AN ADULT WITH HENOCH–SCHÖNLEIN PURPURA SECONDARY TO CORONAVIRUS DISEASE INFECTION - Karanikolić, Vesna; Golubovic, Masa (Acta medicae Medianae, 2024)
Previous upper respiratory tract infection has been identified as the most common factor causing Henoch–Schönlein purpura (HSP). The most common causes of infection are streptococci, followed by viral infections. Upper respiratory tract infection with coronavirus disease (COVID-19) could be an HSP-triggering virus. We present a case of a 39-year-old male who developed HSP in the setting of COVID-19 infection. HSP occurred 14 days after COVID-19 diagnosis and it exhibited itself in the form of the lower extremities and buttocks palpable purpura, lower abdominal pain, nausea and hematuria. The patient was treated with methylprednisone, and meprednisone, which led to rapid clinical improvement. Endothelial damage in patients with COVID-19 viral infection occurs as a consequence of a severe inflammatory reaction. Extremely important place in the inflammatory reaction of the endothelium is occupied by IgA, which can be deposited within the endothelium. This activates other cytokines that can lead to HSP occurrence.
Keywords: coronavirus disease, Henoch–Schönlein purpura, adults